Analisis Konsep Al-Ta’widh pada Ketentuan Ganti Rugi Pakaian Cucian yang Rusak di Jasa Laundry Syariah Arransha Kota Langsa - Indrayani, Dewi; Muttaqin, Zainal; Kurnia, Ryzka Dwi (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2023)
This study aims to analyze the concept of al-ta'widh on the compensation provisions for damaged customer clothes in the Arransha Syariah Laundry service, Langsa City. The research method used is an empirical legal method that originates from primary and secondary qualitative data using descriptive analysis methods. The results of this study reveal: 1). The written compensation provisions applied to the Arransha Syariah Laundry service in Langsa City have not been detailed about the consequences of ignoring the second requirement, that is "check your clothes again before leaving Arransha Laundry". That point resulted complaints from customers who complained about various complaints after the clothes were inspected at each customer's home; 2). The third terms and condition does not specifically mention the types of losses that are entitled to receive 50% compensation. In addition, the requirement for compensation of 50% of the price of damaged clothes is included in the category of damaged conditions (al-syarth al-fasid) whose validity is not recognized by syara'. So that if there is loss, damage & recording of customer clothes that occur during the washing process due to negligence of the laundry or due to violating procedures in the laundry process, 100% compensation (al-ta'widh) according to the quality and quantity of clothes will be charged to the laundry.